Posters 2017
DOI: 10.1136/archdischild-2017-313273.249
|View full text |Cite
|
Sign up to set email alerts
|

P161 Overweight and obesity in romanian children, in european context

Abstract: BackgroundThis survey, part of the European Project JANPA ( Joint Actions for Nutritional and Physical Activities), aims to the evaluation of obesity prevalence in Romanian children versus obesity prevalence in children of six other European countries: Italy, Greece, Portugal, Slovenia, Croatia and Ireland.Material and methodA number of 13 surveys and researches developed in Romania at regional or national scale between 2010 and 2016 concerning prevalence of overweight and obesity in children, have been analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another study determined that 8.29% of children are obese, while 12.84% of them are overweight, with boys being more likely to be obese; the highest prevalence has been observed among the 6–10 years’ age group, while teenagers have recorded the lowest prevalence [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study determined that 8.29% of children are obese, while 12.84% of them are overweight, with boys being more likely to be obese; the highest prevalence has been observed among the 6–10 years’ age group, while teenagers have recorded the lowest prevalence [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 The most recent data for Romania showed that one in four children was overweight or obese with male gender and school-aged groups being more affected. 2 , 3 This condition leads to a higher propensity towards developing metabolic syndrome, diabetes mellitus, hypertension, cardiovascular disease, and sleep apnea both during childhood and later in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…9 Obesity rates for 9.19% out of the first ten chronic diseases in Romanian children. 10 Multicenter studies of prevalence in Romanian children and adolescents showed that 17% to 30% are overweight or obese according to WHO standards 11 , with a range from 31.6% (overweight and obese) to 11.4% (only obese) in the southern part of the country 12 and 18.2% (overweight) and 7.2% (obese) in the western part (IOTF standards). 13 A pooled analysis over a decade (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) showed that the prevalence of overweight (including obese) children was 28.3%/23%/23.2% (WHO/IOTF/CDC) and that the prevalence was stable across the years.…”
Section: Introductionmentioning
confidence: 99%